A call for uniformity in implementing the IPAF (interstitial pneumonia with autoimmune features) criteria. Issue 6 (December 2016) - Jee, Adelle S.; Bleasel, Jane F.; Adelstein, Stephen; Keir, Gregory J.; Corte, Tamera J.
We commend Oldham et al . [1] for their recent article using the new European Respiratory Society/American Thoracic Society criteria for interstitial pneumonia with autoimmune features (IPAF) to re-characterise a cohort of interstitial lung disease (ILD) patients in their centre. IPAF defines individuals with interstitial pneumonia and features suggestive of a connective tissue disease (CTD), but not meeting established CTD classification criteria [2]. Of their 422 patients with previously diagnosed idiopathic interstitial pneumonia (IIP) or undifferentiated-CTD ILD (UCTD-ILD), approximately one-third met the IPAF criteria, including nearly 20% of those with idiopathic pulmonary fibrosis, 25% with unclassifiable IIP and almost all of those with UCTD-ILD [1]. Importantly, survival was markedly worse in the IPAF group compared with a CTD-ILD cohort [1]. Within the IPAF domains, the presence of at least one clinical criterion was predictive of a favourable outcome, while morphological, multi-compartment involvement carried a significantly increased risk of mortality [1]. There is an urgent need to standardise our approach to connective tissue disease classification in ILD and IPAF http://ow.ly/IPm0304nLVV